ChemInform Abstract: Access to Drug Metabolites via C—H Functionalization: Copper‐Catalyzed Aerobic Oxidation of N, N‐Dimethylalkylamines in Complex Pharmaceuticals. Issue 39 (September 2015) - Genovino, Julien; Sames, Dalibor; Toure, B. Barry
Abstract The practical, cost‐effective and operationally simple two‐step transformation is applied to a range of dimethylamine‐containing pharmaceuticals including clomipramine (I) and diltiazem (IV).